Compendium of South African Environmental Legislation - Second Edition - Loretta Feris (Pretoria University Law Press (PULP), 2010)
Compendium of South African Environmental Legislation - Second Edition Edited by Morné van der Linde and Loretta Feris 2010 ISBN: 978-0-9814420-6-8 Pages: vi 690 Print version: Available Electronic version: Free PDF available